FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KEPALA KELUARGA DALAM PENERAPAN DEKLARASI KAWASAN DILARANG MEROKOK (KDM) (Studi di Wilayah Pedukuhan Gluntung Kidul Desa Caturharjo Kecamatan Pandak Kabupaten Bantul) - Inggrid Dwi Kusumaningrum; Priyadi Nugraha Prabamukti; Syamsulhuda BM (Jurnal Kesehatan Masyarakat (Undip), 2018)
Smoking behavior has an impact on health, social, economy, and environment, which does not only occur in active smokers but also in passive smokers. No smoking area (KDM) aims to protect health from the dangers of smoking, cultivate a healthy life, suppress novice smokers, and protect the health of passive smokers. The purpose of this research  is to analyze the factors related to the behavior of the family’s head in the implementation of the declaration of no smoking area (KDM) in Gluntung Kidul Hamlet. The study population was 185 family heads in Gluntung Kidul Hamlet. Sampling technique used the Lemeshow calculation selected by 62 respondents. Data analysis was done univariat, bivariate, and multivariate.The result of this research shows the behavior of the family’s head in the application of the KDM declaration in the Gluntung Kidul area is quite good (54.8%).The majority of respondents were aged 15-64 years (87%), had basic education category (62,9%), worked in the non-formal sector (80.6%) and the length of stay was ≥20 years (88.7%). Variables related to the behavior of the family’s head in the application of KDM are employment (p= 0.035), knowledge (p= 0.015), KDM information facilities (p = 0.024), community leader support (p= 0.030), cadre support (p= 0.048) and health worker support (p= 0.006). Variables that were not related are age, last education, length of stay, the attitude of respondents, access to information, sanctions, family support, and neighbor support. While the most dominant variable is health worker support (p= 0,017) with OR value 5,082.